1992
DOI: 10.1093/oxfordjournals.aje.a116270
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and the Risk of Anogenital Cancer

Abstract: The association between cigarette smoking and cervical cancer has been demonstrated in numerous prior studies. As part of population-based case-control studies of cancers of the vulva, vagina, cervix, anus, and penis in relation to infection with human papillomavirus, conducted in western Washington State and the province of British Columbia from the mid 1980s until the present time, the authors have collected detailed information on smoking history. The proportion of subjects who were current smokers of cigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
4
6

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(129 citation statements)
references
References 0 publications
6
112
4
6
Order By: Relevance
“…Three studies reported that VV-SCC patients tend to have shorter education, lower household incomes and more often belong to lower social strata of society than controls. 2,8,16,17 Our findings regarding tobacco consumption are in agreement with prior reports All univariate odds ratios are adjusted for age at the time of the diagnosis.-2 Numbers and percentages of respondents who reported that they had had the disease (or HIV test) in question. In the calculation of odds ratios for these variables, respondents reporting no such disease (or HIV test) served as the reference group.-3 Numbers and percentages of respondents who reported that their male partner had had the disease in question.…”
Section: Discussionsupporting
confidence: 87%
“…Three studies reported that VV-SCC patients tend to have shorter education, lower household incomes and more often belong to lower social strata of society than controls. 2,8,16,17 Our findings regarding tobacco consumption are in agreement with prior reports All univariate odds ratios are adjusted for age at the time of the diagnosis.-2 Numbers and percentages of respondents who reported that they had had the disease (or HIV test) in question. In the calculation of odds ratios for these variables, respondents reporting no such disease (or HIV test) served as the reference group.-3 Numbers and percentages of respondents who reported that their male partner had had the disease in question.…”
Section: Discussionsupporting
confidence: 87%
“…10 However, concern remains that smoking may be an etiologic factor only among certain subgroups 11 and that confounding by sexual factors may not have been ruled out. To explore this hypothesis, we analyzed the correlation between smoking and anal carinoma for the complete group of men and women in the current study population and then for various subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…5,10,12,19,23 Current smoking at the time of diagnosis has been associated with all HPV-related squamous cell anogenital tumors, regardless of whether HPV DNA is present in the tumor. Because it appears that it is most important if patients with cancer are current smokers at the time of diagnosis, current smoking likely has a promotional effect at late stages of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…There is also mounting evidence that the same types of HPV, particularly type 16, are involved in the aetiology of most anal epidermoid carcinomas (Daling et al, 1992;Holm et al, 1994;Frisch et al, 1997). However, other factors involved in the development of anal cancer are poorly characterized.…”
Section: Discussionmentioning
confidence: 99%